Comparative Analysis of Sleep Behavior in ASD Children: A Taif City Perspective (Bangladesh Journal of Medical Science, 2025)
Background Sleep habits in children with Autism Spectrum Disorder (ASD) are poorly understood despite their significant impact on overall well-being. This study aimed to comprehensively assess sleep behaviors and challenges faced by children diagnosed with ASD in Taif City, targeting individuals under 15 years old. Methodology A cohort of 130 participants, including 41 autistic children and 89 typically developing controls, was recruited using convenience and snowball sampling. Data collection involved analyzing bedtime and wake-up patterns, sleep duration, and specific sleep-related issues. Statistical analyses compared findings between the two groups. Results Autistic children exhibited distinct sleep behavior patterns compared to controls. They showed earlier bedtimes, consistent wake-up times—often earlier than controls— and notably shorter sleep durations (p